A preliminary annotated bibliography of materials on Sino-Philippine relations available in selected libraries in Metro Manila, 1975-1984 - Zhou Kangmei, 1951-; Buenrostro, Juan Jr. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1986)
The purpose of this study is to conduct a preliminary survey of materials on Sino-Philippine relations available in selected libraries in Metro Manila from 1975 to 1984 and compile an annotated list of these materials to facilitate their use and help the researchers who are conducting literature searches on the subject.
More than ten libraries located in the Metro Manila area were visited to gather bibliographical data on materials related to Sino-Philippine relations from 1975-1984.The bibliography includes 1,013 entries of which 19 are theses, 4 class reports and occasional papers, 35 books, 539 articles in magazines, and 435 newspaper articles and editorials.
The subject of the relations between the two countries covers diplomatic, cultural, trade and scientific and technical areas. The bibliography is arranged in straight alphabetical order by subject headings regardless of type of materials. The list of subject headings of the Library of Congress was used in determining the subject of the documents. Under the subject headings, entries are arranged chronologically by year of publication. A general author and title index is provided at the end of the bibliography. A brief account of the development of the relations between China and the Philippines is given in Chapter II for a better understanding of the work.
Mimeographed.
Special Problem (Master of Library Science)
Keywords: China -- Foreign Relations -- Bibliography. -- Philippines; Philippines -- Foreign Relations -- Bibliography. -- China